PENGARUH LATIHAN PULL OVER TERHADAP KEMAMPUAN SMASH PADA PERMAINAN BULUTANGKIS - Sudiadharma, Sudiadharma; Ishak, Muhammad (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to determine the effect of pull over training on smash ability in badminton games. This research is experimental. The population is UNM FIK students. The sample used was 20 people consisting of 10 people in each training group. The sampling technique is ordinal matching. The data analysis technique used was descriptive analysis, requirements test, and t-test at a significant level of 95% or 0.05. The results showed that: (1) There was a significant effect of pull over training on smash ability in badminton games, with the value of t count = -11,000 <from t table = 1,833 at a significant level of 95% or 0.05. (2) There is an insignificant influence of the control group on smash ability in badminton games. The value of t count = -6,000 <from t table = 1,833 at a significant level of 95% or 0.05. (3) There is a difference in effect between pull over and control groups on smash ability in badminton games by obtaining t count = 3.674> from t table = 1.833 and P value (0.546> 0.05)